2016
DOI: 10.1186/s13561-016-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-authorisation measures from regulatory authorities with additional evidence requirements from the HTA body in Germany – are additional data requirements by the Federal Joint Committee justified?

Abstract: ObjectivesThe aim of this study was to compare post-authorisation measures (PAMs) from the European Medicines Agency (EMA) with data requests in fixed-termed conditional appraisals of early benefit assessments from the German Federal Joint Committee (G-BA).MethodsMedicinal products with completed benefit assessments during an assessment period of 3.5 years were considered. PAMs extracted from European Public Assessment Reports (EPARs) were compared with data requests issued by the G-BA in the context of condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Our survey respondents suggested that the requirements need to be aligned not only at the initial approval stage but also during postauthorization to best fulfill the follow-up evidentiary requirements of regulatory and HTA agencies. A recent study by Ruof et al [24] assessed the postauthorization data request from EMA and the German HTA body Der Gemeinsame Bundesausschuss (G-BA), and found that G-BA made additional requests with less clear instructions compared with those made by the EMA.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey respondents suggested that the requirements need to be aligned not only at the initial approval stage but also during postauthorization to best fulfill the follow-up evidentiary requirements of regulatory and HTA agencies. A recent study by Ruof et al [24] assessed the postauthorization data request from EMA and the German HTA body Der Gemeinsame Bundesausschuss (G-BA), and found that G-BA made additional requests with less clear instructions compared with those made by the EMA.…”
Section: Discussionmentioning
confidence: 99%
“…Within their report on the implementation of the EMA-EUnetHTA work plan 2017–2021 EMA and EUnetHTA provide in-depth insights regarding their discussion of controversial methodological challenges [ 15 ]. Continuation of those discussions and clarification of evidence requirements within the regulatory and HTA framework including parallel early advice, early access schemes, as well as regulatory and HTAs is urgently required to ‘ensuring a strong EU voice globally’ in line with chapter 5 of the European Commission’s pharmaceutical strategy for Europe [ 13 , 16 , 17 ]. The management of uncertainty after successful EMA approval leading to additional national data requirements as a toll needed for covering the gaps and discrepancies between the regulatory and HTA data needs is another key challenge affecting any future oncology HTA within Europe [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within their report on the implementation of the EMA-EUnetHTA work plan 2017–2021 EMA and EUnetHTA provide in-depth insights regarding their discussion of controversial methodological challenges [ 15 ]. Continuation of those discussions and clarification of evidence requirements within the regulatory and HTA framework including parallel early advice, early access schemes, as well as regulatory and HTAs is urgently required to ‘ensuring a strong EU voice globally’ in line with chapter 5 of the European Commission’s pharmaceutical strategy for Europe [ 13 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two-step process begins with an early benefit assessment initiated at the launch of the pharmaceutical. The objective of the early benefit assessment is to assess whether a pharmaceutical has an additional benefit in comparison to the appropriate comparator therapy (ACT) 5 , 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%